(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the importance of developing the emotional intelligence (EQ) of pupils and students in the modern education system and explores advanced technologies in this field. The research highlights interactive methods and psychological approaches aimed at managing emotions, developing empathy, and building social skills. Furthermore, the impact of emotional intelligence on academic achievement and personal success is substantiated throught international experiences.